Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To identify the mistake in solving the equation [tex]\(6x - 1 = -2x + 9\)[/tex], let's go through each step methodically and check for correctness and proper justifications:
1. Starting equation:
[tex]\(6x - 1 = -2x + 9\)[/tex]
2. Combining like terms:
Adding [tex]\(2x\)[/tex] to both sides of the equation to combine like terms on one side.
[tex]\[ 6x - 1 + 2x = -2x + 9 + 2x \][/tex]
Simplifies to:
[tex]\[ 8x - 1 = 9 \][/tex]
The justification for this step is the Addition property of equality, which is correctly applied.
3. Removing the constant term from one side:
Adding 1 to both sides to isolate the term involving `x`.
[tex]\[ 8x - 1 + 1 = 9 + 1 \][/tex]
Simplifies to:
[tex]\[ 8x = 10 \][/tex]
The justification for this step is the Addition property of equality, which is correctly applied.
4. Solving for [tex]\(x\)[/tex]:
Dividing both sides by 8 to solve for `x`.
[tex]\[ \frac{8x}{8} = \frac{10}{8} \][/tex]
Simplifies to:
[tex]\[ x = \frac{10}{8} \][/tex]
The justification for this step is the Division property of equality, which is correctly applied.
5. Simplifying the fraction:
Simplifying the fraction:
[tex]\[ x = \frac{10}{8} = \frac{5}{4} \][/tex]
Given the process, we notice an inconsistency in the provided solution steps. In step 4, the simplification results in:
[tex]\[ x = \frac{10}{8} \][/tex]
However, there's a mistake in stating the intermediate result directly as:
[tex]\[ x = \frac{8}{10} \][/tex]
This is incorrect since it should be [tex]\(x = \frac{10}{8}\)[/tex].
Therefore, the correct answer that identifies the mistake is:
C. Step 3 is incorrect and should be [tex]\( x = \frac{10}{8} \)[/tex].
1. Starting equation:
[tex]\(6x - 1 = -2x + 9\)[/tex]
2. Combining like terms:
Adding [tex]\(2x\)[/tex] to both sides of the equation to combine like terms on one side.
[tex]\[ 6x - 1 + 2x = -2x + 9 + 2x \][/tex]
Simplifies to:
[tex]\[ 8x - 1 = 9 \][/tex]
The justification for this step is the Addition property of equality, which is correctly applied.
3. Removing the constant term from one side:
Adding 1 to both sides to isolate the term involving `x`.
[tex]\[ 8x - 1 + 1 = 9 + 1 \][/tex]
Simplifies to:
[tex]\[ 8x = 10 \][/tex]
The justification for this step is the Addition property of equality, which is correctly applied.
4. Solving for [tex]\(x\)[/tex]:
Dividing both sides by 8 to solve for `x`.
[tex]\[ \frac{8x}{8} = \frac{10}{8} \][/tex]
Simplifies to:
[tex]\[ x = \frac{10}{8} \][/tex]
The justification for this step is the Division property of equality, which is correctly applied.
5. Simplifying the fraction:
Simplifying the fraction:
[tex]\[ x = \frac{10}{8} = \frac{5}{4} \][/tex]
Given the process, we notice an inconsistency in the provided solution steps. In step 4, the simplification results in:
[tex]\[ x = \frac{10}{8} \][/tex]
However, there's a mistake in stating the intermediate result directly as:
[tex]\[ x = \frac{8}{10} \][/tex]
This is incorrect since it should be [tex]\(x = \frac{10}{8}\)[/tex].
Therefore, the correct answer that identifies the mistake is:
C. Step 3 is incorrect and should be [tex]\( x = \frac{10}{8} \)[/tex].
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.